Greenfield FDI Inflows in Selected Emerging European Economies with Reflections on External Balance - Ercegovac, Dajana; Beker Pucar, Emilija (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
The research objective is to identify the main locations for greenfield FDI inflows as well as to analyze related external balance in selected Emerging European Economies (EEEs) in order to suggest useful implications towards economic policy creators in Western Balkans. The authors conducted original descriptive statistical analysis on the data available in UNCTAD, FDI/MNE and World Bank database in the time period 2008-2019. The analysis of average greenfield FDI inflows and trading balance in GDP includes following country groups: Visegrad States, Baltic States, Western Balkans and eleven new EU member states in the period after the structural break of Global Financial Crisis (GFC). The results suggest that the Visegrad States (particularly Poland) were the most attractive locations for greenfield investments in the analyzed time period. Also, analyzed group of countries had the strongest improvements in external balance with surplus position since 2013. Having in mind the results of this study and the positive effects of significant greenfield FDI inflows given in the existing literature, we suggest that Western Balkan countries should implement adequate measures to attract greater greenfield FDI inflows in order to stimulate export oriented production, sustainable development and real convergence towards developed European economies. The suggested connection implies further research and verification using panel data analysis in selected EEEs.